Randomized, placebo-controlled trial evaluating the safety of one-year administration of green tea catechins - Kumar, Nagi B; Pow-Sang, Julio; Spiess, Philippe E; Park, Jong; Salup, Raoul; Williams, Christopher R; Parnes, Howard; Schell, Michael J (Oncotarget, 2016)
Although preclinical, epidemiological and prior clinical trial data suggest that green tea catechins (GTCs) may reduce prostate cancer (PCa) risk, several preclinical studies and case reports have reported liver toxicities and acute gastrointestinal bleeding. Based on these observations, regulatory bodies have required stringent inclusion criteria with frequent, excessive toxicity monitoring and early stopping rules in clinical trials. These requirements have impeded recruitment and retention of subjects in chemoprevention trials and subsequent progress in agent development efforts. We conducted a placebo-controlled, randomized clinical trial of Polyphenon E® (PolyE®), a proprietary mixture of decaffeinated GTCs, containing 400 mg (-)-epigallocatechin-3-gallate (EGCG) per day, in 97 men with high-grade prostatic intraepithelial neoplasia (HGPIN) and/or atypical small acinar proliferation (ASAP). PolyE® containing 200 mg EGCG was administered with food, BID. A secondary study endpoint in this trial was a comparison of the overall one-year treatment related adverse events and grade 3 or higher adverse event on the two study arms. Monthly assessments of toxicity (CTCAE 4.0), concomitant medications and organ function, including hepatic panel, PT/PTT and LDH, were performed. Daily intake of a standardized, decaffeinated, catechin mixture containing 200 mg EGCG BID taken with food for 1 year accumulated in plasma and was well tolerated and did not produce treatment related adverse effects in men with baseline HGPIN or ASAP. The current data provides evidence of safety of decaffeinated, catechin mixture containing 200 mg EGCG BID to be further tested for prostate cancer prevention or other indications.